Does Matching Roussouly Spinal Shape and Improvement in SRS-Schwab Modifier Contribute to Improved Patient-reported Outcomes?. Issue 18 (15th September 2021) - Passias, Peter G.; Pierce, Katherine E.; Raman, Tina; Bortz, Cole; Alas, Haddy; Brown, Avery; Ahmad, Waleed; Naessig, Sara; Krol, Oscar; Passfall, Lara; Kummer, Nicholas A.; Lafage, Renaud; et al.
Abstract : Study Design: Retrospective review. Objective: The aim of this study was to evaluate outcomes of matching Roussouly and improving in Schwab modifier following adult spinal deformity (ASD) surgery. Summary of Background Data: The Roussouly Classification system of sagittal spinal shape and the SRS-Schwab classification system have become important indicators of spine deformity. No previous studies have examined the outcomes of matching both Roussouly type and improving in Schwab modifiers postoperatively. Methods: Surgical ASD patients with available baseline (BL) and 1 year (1Y) radiographic data were isolated in the single-center spine database. Patients were classified by their "theoretical" and "current" Roussouly types as previously published. Patients were considered a "Match" if their theoretical and current Roussouly types were the same, or a "Mismatch" if the types differed. Patients were noted as improved if they were Roussouly "Mismatch" preoperatively, and "Match" at 1Y postop. Schwab modifiers at BL were categorized as follows: no deformity (0), moderate deformity (+), and severe deformity (++) for PT, SVA, and PI-LL. Improvement in SRS-Schwab was defined as a decrease in any modifier severity at 1Y. Results: 103 operative ASD patients (61.8 years, 63.1% female, 30 kg/m 2 ) were included. At baseline, breakdown of "current" Roussouly type was: 28% Type 1, 25.3% Type 2, 32.0% Type 3, 14.7% Type 4. 65.3% of patients were classified as Roussouly "Mismatch" at BL. Breakdown of BL Schwab modifier severity: PT (+: 41.7%, ++: 49.5%), SVA (+: 20.3%, ++: 50%), PI-LL (+: 25.2%, ++: 46.6%). At 1 year postop, 19.2% of patients had Roussouly "Match". Analysis of Schwab modifiers showed that 12.6% improved in SVA, 42.7% in PI-LL, and 45.6% in PT. Count of patients who both had a Roussouly type "Match" at 1Y and improved in Schwab modifier severity: nine PT (8.7%), eight PI-LL (7.8%), and two SVA (1.9%). There were two patients (1.9%) who met their Roussouly type and improved in all three Schwab. 1Y matched Roussouly patients improved more in health-related quality of life scores (minimal clinically important difference [MCID] for Oswestry Disability Index [ODI], EuroQol-5D-3L [EQ5D], Visual Analogue Score Leg/Back Pain), compared to mismatched, but was not significant ( P > 0.05). Match Roussouly and improvement in PT Schwab met MCID for EQ5D more ( P = 0.050). Matched Roussouly and improvement in SVA Schwab met MCID for ODI more ( P = 0.024). Conclusion: Patients who both matched Roussouly sagittal spinal type and improved in SRS-Schwab modifiers had superior patient-reported outcomes. Utilizing both classification systems in surgical decision-making can optimize postop outcomes. Level of Evidence: 3 Abstract : This study attempted to evaluate the outcomes of optimal adult spinal deformity correction of both the SRS-Schwab and Roussouly recommended classifications at 1 year at a single academic institution. Patients who both matched Roussouly sagittal spinal type and improved in SRS-Schwab modifiers had superior patient-reported outcomes at 1 year.